The influence of Islamic modernization on Islamic education in Egypt in the early 19th century - Fergina, Ana; Hifza, Hifza; Achruch, Andi (Academy of Education Journal, 2024)
Education is essential in the life of a society because, through it, people can learn science and technology. Modernization in Islamic education needs to be carried out to catch up with backwardness in all fields in Egypt. This article aims to describe the history of Islam and the modernization of Islamic education in Egypt. Starting from modern ideas from the West brought by the colonizing nation, Egypt was able to rise from adversity and catch up by giving birth to modern reformers. Reforms in education made Al Azhar a leading center for studies in the Middle East.